2016
DOI: 10.1177/1470320316647239
|View full text |Cite
|
Sign up to set email alerts
|

Quinapril decreases antifibrinolytic and prooxidative potential of propofol in arterial thrombosis in hypertensive rats

Abstract: Angiotensin converting enzyme inhibitors and propofol both exert hypotensive action and may affect hemostasis. We investigated the influence of quinapril and propofol on hemodynamics and hemostasis in renal-hypertensive rats with induced arterial thrombosis. Two-kidney, one clip hypertensive rats were treated with quinapril (3.0 mg/kg for 10 days), and then received propofol infusion (15 mg/kg/h) during ongoing arterial thrombosis. The hemodynamic and hemostatic parameters were assayed. Quinapril exerted a hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 66 publications
0
19
0
Order By: Relevance
“…In turn, our earlier studies ( Kramkowski et al, 2006 ; Wojewodzka-Zelezniakowicz et al, 2006 , 2016 ) clearly showed that angiotensin converting enzyme inhibitors (ACE-Is) improve endothelial function in a mechanism involving, among others, BK increase. In the same model of thrombosis, ACE-Is decreased thrombus weight, prolonged the time to carotid artery occlusion, increased blood flow distally to the place of vessel injury and decreased collagen-stimulated whole blood platelet aggregation.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…In turn, our earlier studies ( Kramkowski et al, 2006 ; Wojewodzka-Zelezniakowicz et al, 2006 , 2016 ) clearly showed that angiotensin converting enzyme inhibitors (ACE-Is) improve endothelial function in a mechanism involving, among others, BK increase. In the same model of thrombosis, ACE-Is decreased thrombus weight, prolonged the time to carotid artery occlusion, increased blood flow distally to the place of vessel injury and decreased collagen-stimulated whole blood platelet aggregation.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore the bleeding time method is used to investigate the primary haemostasis. After vessel wall injury and following vasoconstriction platelets accumulate at the site of the injury to form platelet plug ( Wojewodzka-Zelezniakowicz et al, 2016 ). Prolonged bleeding time clearly indicate the involvement of platelets inhibition in the antithrombotic effect of tormentil extract.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 Also, an increase in tissue plasminogen activator (t-PA) and decrease in tissue plasminogen activator inhibitor (PAI-1) concentration were observed. 7 …”
Section: Introductionmentioning
confidence: 99%